Some trials for control of sheep scab in Siwa Oasis - Mohamed Ali Mohamed Gebely; Amal Abdelaziz Elmolla; Salwa Mahmoud Mahmoud Habeeb; Waheed Mohamed Ali Moussa (Cairo : Mohamed Ali Mohamed Gebely, 2012)
The epidemiology of the disease was investigated on 1647 sheep from different localities in Siwa oasis . Skin scrapings were collected from sheep showing signs of sarcoptes infestation which was confirmed in 181 sheep after parasitological examination . The effect of seasonal variation on the prevalence of sarcoptes was studied and the highest prevalence was detected in the winter also the effect of age on the prevalence of sarcoptes was studied and the highest prevalence was detected in the sheep aging between 2 and 3 years
Thesis (Ph.D.) - Cairo University - Faculty of Veterinary Medicine - Department of Internal Medicine and Infections Diseases
Issued also as CD
Keywords: Mange; Sarcoptes; Siwa oasis